Factors Affecting the Sleep Quality of Patients in the Intensive Care Unit - Barkah Waladani; Endah Setianingsih; Juni Sofiana (Babali Health, 2022)
Introduction: The condition of the patient in the intensive room and the environmental conditions that occur in the intensive room can affect the quality of the patient's sleep. The purpose of this study was to determine the factors that influence the quality of sleep of patients in the intensive care unit. Methods: This research is a type of quantitative research using descriptive analytical methods. The time approach used is cross- sectional. The sample in this study amounted to 90 respondents. Results: The results showed that the p value of each factor was physical factor p 0.027, noise p 0.020, lighting p 0.043, and activity p 0.000. The p value of the 4 factors is smaller than <0.05, thus indicating that physical variables, noise, lighting and activity have an influence on sleep quality. The strength of the relationship can be seen from the value of OR (EXP [B]), seen from the largest to the smallest values are activity (OR: 5,686), lighting (OR: 2,781), physical (2,040) and noise (OR: 1,491). Based on these results, the most influencing factor for sleep quality is activity. Conclusion: The conclusion of this study is that the factors that affect sleep quality are physical, noise, lighting, and activity. The most influencing factor for sleep quality is activity. Recommendations that can be done are to suppress or reduce factors that affect sleep quality.